2016
DOI: 10.1007/s12035-016-0219-2
|View full text |Cite
|
Sign up to set email alerts
|

Roles of HIF-1α, VEGF, and NF-κB in Ischemic Preconditioning-Mediated Neuroprotection of Hippocampal CA1 Pyramidal Neurons Against a Subsequent Transient Cerebral Ischemia

Abstract: Ischemic preconditioning (IPC) provides neuroprotection against subsequent severe ischemic insults by specific mechanisms. We tested the hypothesis that IPC attenuates post-ischemic neuronal death in the gerbil hippocampal CA1 region (CA1) throughout hypoxia inducible factor-1α (HIF-1α) and its associated factors such as vascular endothelial growth factor (VEGF) and nuclear factor-kappa B (NF-κB). Lethal ischemia (LI) without IPC increased expressions of HIF-1α, VEGF, and p-IκB-α (/and translocation of NF-κB p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 65 publications
3
30
0
Order By: Relevance
“…Meanwhile, NAD + and NADP + both activate K Na 1.2 presumably via this nucleotide-binding domain [298], but it should be noted that pyridine nucleotides can also act on K ATP [299] and K Ca channels [300,301], so this property cannot be used to distinguish these channels. Interestingly, in neurons of both humans and rats, K Na 1.2 transcription is regulated by nuclear factor kappa B (NF-κB) activation [302], which itself is activated by IPC and APC [303306]. Knockout mice for Kcnt1 , Kcnt2 , and a double knockout are available and have been used to determine the role of these channels in cardioprotection (see below) [89,307].…”
Section: Mitochondrial Kna1x Channelsmentioning
confidence: 99%
“…Meanwhile, NAD + and NADP + both activate K Na 1.2 presumably via this nucleotide-binding domain [298], but it should be noted that pyridine nucleotides can also act on K ATP [299] and K Ca channels [300,301], so this property cannot be used to distinguish these channels. Interestingly, in neurons of both humans and rats, K Na 1.2 transcription is regulated by nuclear factor kappa B (NF-κB) activation [302], which itself is activated by IPC and APC [303306]. Knockout mice for Kcnt1 , Kcnt2 , and a double knockout are available and have been used to determine the role of these channels in cardioprotection (see below) [89,307].…”
Section: Mitochondrial Kna1x Channelsmentioning
confidence: 99%
“…In this study, we assume VEGF was regulated in two ways. It has been reported that NFκB signaling induces angiogenesis by increasing the production of VEGF [44][45][46], angiogenesis induced by MUC3A is also mediated by NFκB activation in NSCLC. Radiation-mediate hypoxia triggers HIF-1α transcription and up-regulates VEGF expression [46,47], MUC3A knockdown may enhance radiosensitivity by promoting oxygen stress and impair HIF-1α and VEGF expression level.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia conditions can trigger the generation of hypoxiainducible factor-1α (HIF-1α), which is an oxygen-sensitive transcription factor. It can be significantly upregulated after cerebral ischemia and then participate in regulating the expression of various genes, thereby triggering various physiological responses (123)(124)(125)(126)(127)(128)(129). IPreC has different effects on the expression of HIF-1α in different cells, and it can increase the expression of HIF-1α in neurons quickly and transiently but slowly and continuously in astrocytes (130).…”
Section: Hypoxia Inducible Factormentioning
confidence: 99%
“…However, astrocytic HIF-1α was independent of PHD2, which allows astrocytes to cause long-lasting HIF-1α expression and was rather essential for induction of ischemic tolerance efficiently (132). IPreC can also attenuate neuronal death induced by ischemic insults in the gerbil hippocampal CA1 region (CA1) throughout upregulation of HIF-1α, which enhances vascular endothelial growth factor (VEGF) expression and nuclear factor-kappa B (NF-κB) activation (125).…”
Section: Hypoxia Inducible Factormentioning
confidence: 99%